An Improved Auto-Calibration Algorithm Based on Sparse Bayesian Learning Framework - Lifan Zhao; Guoan Bi; Lu Wang; Haijian Zhang (IEEE signal processing letters, 2013)
This letter considers the multiplicative perturbation problem in compressive sensing, which has become an increasingly important issue on obtaining robust performance for practical applications. The problem is formulated in a probabilistic model and an auto-calibration sparse Bayesian learning algorithm is proposed. In this algorithm, signal and perturbation are iteratively estimated to achieve sparsity by leveraging a variational Bayesian expectation maximization technique. Results from numerical experiments have demonstrated that the proposed algorithm has achieved improvements on the accuracy of signal reconstruction.